The contribution of the family farm for rural development in Mato Grosso do Sul state - Brazil - Sangalli, Adriana Rita (2013)
This article aims to analyze the contribution of family farming for rural development in the state of Mato Grosso do Sul. The methodology used was based on data from the 2006 Agricultural Census, conducted by the Brazilian Institute of Geography and Statistics (IBGE), beyond literature review, addressing aspects of family and employer agriculture, as well as the familiar and unfamiliar agribusiness GDP. The data presented showed that family farming adds the largest number of persons employed in Brazil , while in Mato Grosso do Sul, dominates the highest number of persons employed in agriculture employer. The Gross Domestic Product analyzed had a growing, performance, revealing that the productive potential of family farming contributes significantly to the development of the State of Mato Grosso do Sul.